Proband Whole-Exome Sequencing Identified Genes Responsible for Autosomal Recessive Non-Syndromic Hearing Loss in 33 Chinese Nuclear Families - Sang, Shushan; Ling, Jie; Liu, Xuezhong; Mei, Lingyun; Cai, Xinzhang; Li, Taoxi; Li, Wu; Li, Meng; Wen, Jie; Liu, Xianlin; Liu, Jing; Liu, Yalan; et al. (Frontiers in Genetics, 2019)
Autosomal recessive non-syndromic hearing loss (ARNSHL) is an extremely genetic heterogeneous disease with more than seventy pathogenic genes. However, most ARNSHL families are small-sized pedigrees with limited genetic information, challenging the molecular diagnosis for these patients. Therefore, we attempted to establish a strategy for identifying causing variants with ARNSHL by applying proband-based whole exome sequencing (proband-WES). Besides wishing to improve the molecular diagnostic rates, we also expected to search for novel deafness genes shared by patients with similar phenotype, making up the deficiency of small-sized ARNSHL families. In this study, 54.5% (18/33) families were detected pathogenic variants in known deafness genes, most of which were novel variants. Among them, a family with two affected brothers was detected a potential digenic inheritance involving the CDH23 and MYO7A, which was a first report worldwide. We also screened out three novel genes (TRPM2, PTPRG and AHI1) which could be considered as candidate deafness genes. By the way, there was no novel genes shared by various pedigrees, indicating that a larger sample size might be needed. The strategy of proband-WES is a cost-effective and precise way of identifying causative variants in nuclear families with ARNSHL. This economic strategy may be extended to clinical application to provide molecular diagnostic, genetic counseling and individualized health maintenance measures for patients with ARNSHL at hearing clinic.